Patient-physician discordance in assessment of adherence to inhaled controller medication: a cross-sectional analysis of two cohorts - Jácome, Cristina (2019)
We aimed to compare patient's and physician's ratings of inhaled medication adherence and to identify predictors of patient-physician discordance.